2019
DOI: 10.1007/s00018-019-03104-6
|View full text |Cite
|
Sign up to set email alerts
|

Human placenta and trophoblast development: key molecular mechanisms and model systems

Abstract: Abnormal placentation is considered as an underlying cause of various pregnancy complications such as miscarriage, pre eclampsia and intrauterine growth restriction, the latter increasing the risk for the development of severe disorders in later life such as cardiovascular disease and type 2 diabetes. Despite their importance, the molecular mechanisms governing human placental formation and trophoblast cell lineage specification and differentiation have been poorly unravelled, mostly due to the lack of appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
574
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(589 citation statements)
references
References 210 publications
(279 reference statements)
7
574
0
8
Order By: Relevance
“…An alternative approach to obtaining trophoblast cell lines has been to isolate primary trophoblasts from early first trimester placental tissue 22 . It is postulated that a TSC niche resides in the early human first trimester placenta 8,[22][23][24] , where these cells are a proliferative, less differentiated progenitor cell population that gives rise to both villous cytotrophoblasts that fuse to form the syncytia as well as extravillous trophoblast (EVT) progenitor cells at the cell column tips 25 .…”
Section: Introduction (Main Text Not Including Abstract Methods Refmentioning
confidence: 99%
“…An alternative approach to obtaining trophoblast cell lines has been to isolate primary trophoblasts from early first trimester placental tissue 22 . It is postulated that a TSC niche resides in the early human first trimester placenta 8,[22][23][24] , where these cells are a proliferative, less differentiated progenitor cell population that gives rise to both villous cytotrophoblasts that fuse to form the syncytia as well as extravillous trophoblast (EVT) progenitor cells at the cell column tips 25 .…”
Section: Introduction (Main Text Not Including Abstract Methods Refmentioning
confidence: 99%
“…In contrast to mouse, the earliest stage of human placentation is associated with the formation of a zone of invasive primitive syncytium at the blastocyst implantation site (Boss, Chamley, & James, 2018;James, Carter, & Chamley, 2012;Knofler et al, 2019). Later, columns of CTB progenitors penetrate the primitive syncytium to form primary villi.…”
Section: Introductionmentioning
confidence: 99%
“…Later, columns of CTB progenitors penetrate the primitive syncytium to form primary villi. With the progression of pregnancy, primary villi eventually branch and mature to form the villous placenta, containing two types of matured villi; (i) anchoring villi, which anchor to maternal tissue and (ii) floating villi, which float in the maternal blood of the intervillous space (Boss et al, 2018;James et al, 2012;Knofler et al, 2019). The proliferating CTBs within anchoring and floating villi adapt distinct differentiation fates during placentation (Haider et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier microarray study on in vitro differentiating cytotrophoblasts identified expression changes of genes and gene clusters related to structural and functional differentiation of cytotrophoblasts [5,6]. Functional experiments utilizing cytotrophoblasts isolated from healthy term placentas found that the reprogramming of the villous trophoblast transcriptome during differentiation and the unique transcriptomic activity of the syncytiotrophoblast [27] were partly governed by cAMP through the protein kinase A (PKA) or Epac pathways [2,[5][6][7][8][9]11,12,[28][29][30][31][32]. To some extent, the morphological (syncytialization) and biochemical differentiation of cytotrophoblasts may be separate [11,12]: Epac signaling may regulate syncytialization while both Epac and PKA signaling may be involved in biochemical differentiation [2,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia, a life-threatening obstetrical syndrome related to placental dysfunction [32,[57][58][59][60][61][62][63][64][65], is associated with dysregulated expression or function of many PPE proteins (e.g., CGB, LEP), transcription factors (e.g., GCM1, ESRRG), and signaling and kinase pathways (e.g., ERK1/2, p38), especially when it develops preterm [19,57,[66][67][68][69][70][71][72][73][74][75]. Based on the observations that the volume [76] and cellular architecture [67][68][69][77][78][79] of villous trophoblasts are severely impacted in preterm preeclampsia, it has been proposed that either the entire cytotrophoblast differentiation program [80], or particularly syncytialization [81][82][83][84][85][86][87], are affected in preterm preeclampsia, although neither have been proven at the systems level yet.…”
Section: Introductionmentioning
confidence: 99%